Investigating the BSA protein adsorption and bacterial adhesion of Al‐alloy surfaces after creating a hierarchical (micro/nano) superhydrophobic structure. Issue 9 (6th May 2016) - Moazzam, Parisa; Razmjou, Amir; Golabi, Mohsen; Shokri, Dariush; Landarani‐Isfahani, Amir
Abstract: Bacterial adhesion and subsequent biofilm formation on metals such as aluminum (Al) alloys lead to serious issues in biomedical and industrial fields from both an economical and health perspective. Here, we showed that a careful manipulation of Al surface characteristics via a facile two‐steps superhydrophobic modification can provide not only biocompatibility and an ability to control protein adsorption and bacterial adhesion, but also address the issue of apparent long‐term toxicity of Al‐alloys. To find out the roles of surface characteristics, surface modification and protein adsorption on microbial adhesion and biofilm formation, the surfaces were systematically characterized by SEM, EDX, XPS, AFM, FTIR, water contact angle (WCA) goniometry, surface free energy (SFE) measurement, MTT, Bradford, Lowry and microtiter plate assays and also flow‐cytometry and potentiostat analyses. Results showed that WCA and SFE changed from 70° to 163° and 36.3 to 0.13 mN m −1, respectively. The stable and durable modification led to a substantial reduction in static/dynamic BSA adsorption. The effect of such a treatment on the biofilm formation was analyzed by using three different bacteria of Pseudomonas aeruginosa, Staphylococcus epidermidis, and Staphylococcus aureus . The microtiter plate assay and flow cytometry analysis showed that the modification not only could substantially reduce the bacterial adhesion but this biofouling resistance is independent of bacterium type. An excellent cell viability after exposure of HeLa cells to waters incubated with the modified samples was observed. Finally, the corrosion rate reduced sharply from 856.6 to 0.119 MPY after superhydrophobic modifications, which is an excellent stable corrosion inhibition property. © 2016 Wiley Periodicals, Inc. J Biomed Mater Res Part A: 104A: 2220–2233, 2016.